2003
DOI: 10.1063/1.1604251
|View full text |Cite
|
Sign up to set email alerts
|

Can potentially useful dynamics to solve complex problems emerge from constrained chaos and/or chaotic itinerancy?

Abstract: Complex dynamics including chaos in systems with large but finite degrees of freedom are considered from the viewpoint that they would play important roles in complex functioning and controlling of biological systems including the brain, also in complex structure formations in nature. As an example of them, the computer experiments of complex dynamics occurring in a recurrent neural network model are shown. Instabilities, itinerancies, or localization in state space are investigated by means of numerical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…We confirmed that chaotic dynamics introduced in the network does not so sensitively depend on the size of the neuron number (Nara 2003). However, if N is too small, chaotic dynamics can not occur; whereas if N is oversized, it results in excessive computing time.…”
Section: Motion Control and Memory Patternssupporting
confidence: 62%
See 3 more Smart Citations
“…We confirmed that chaotic dynamics introduced in the network does not so sensitively depend on the size of the neuron number (Nara 2003). However, if N is too small, chaotic dynamics can not occur; whereas if N is oversized, it results in excessive computing time.…”
Section: Motion Control and Memory Patternssupporting
confidence: 62%
“…This method was confirmed to be effective to avoid spurious attractors that affect L attractors with K-step maps embedded in the network when connectivity r = N (Nara andDavis 1992, 1997;Nara et al 1993Nara et al , 1995Nara 2003;Suemitsu and Nara 2003).…”
Section: Chaotic Dynamics In a Recurrent Neural Network Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, Nara and Davis have been studying the functional role of chaotic dynamics in a recurrent neural network of binary neurons (abbreviated as NN hereafter) (Davis and Nara 1990;Nara and Davis 1992;Nara et al 1995;Mikami and Nara 2003;Nara 2003;Suemitsu and Nara 2004). They have also shown, in their series of papers, that complex dynamics generated by Cellular Automata (abbreviated as CA hereafter) could be useful in the sense that CA can describe or reproduce arbitrarily given or observed complex dynamics with use of the rule dynamics of CA.…”
Section: Introductionmentioning
confidence: 99%